2014
DOI: 10.14742/ajet.242
|View full text |Cite
|
Sign up to set email alerts
|

Students' self-regulated learning, online information evaluative standards and online academic searching strategies

Abstract: Online information searching strategies (OISS) used by students can be viewed as a key indicator in online learning environments. Therefore, developments in their OISS may also involve variables such as self-regulated learning (SRL) and online information evaluative standards (OIES). Three instruments, an OISS, a SRL and an OIES were used to investigate the roles of SRL (including basic and advanced SRL) and OIES (including naive and advanced standards) in the OISS of 307 high school students in Taiwan. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
1
9
0
5
Order By: Relevance
“…[34] As indicated by Tella, Tella, Ayeni and Omoba, [35] learners' capacity to collect and analyse data adequately is a transferable skill that is valuable for their future, with search strategies being essential for students to complete their tasks. [36] The findings from this study revealed that a number of search engines were used by the respondents, the majority using Google (96.5%), these findings being similar to Malik and Mahmood's [15] study, who found that the majority of respondents (97%) also used Google search engine. Similarly, a study by Experian Hitwise [37] found that Google was the leading search engines used by 65.38% of the study respondents.…”
Section: Discussionsupporting
confidence: 83%
“…[34] As indicated by Tella, Tella, Ayeni and Omoba, [35] learners' capacity to collect and analyse data adequately is a transferable skill that is valuable for their future, with search strategies being essential for students to complete their tasks. [36] The findings from this study revealed that a number of search engines were used by the respondents, the majority using Google (96.5%), these findings being similar to Malik and Mahmood's [15] study, who found that the majority of respondents (97%) also used Google search engine. Similarly, a study by Experian Hitwise [37] found that Google was the leading search engines used by 65.38% of the study respondents.…”
Section: Discussionsupporting
confidence: 83%
“…Researchers found that learners' online self-regulation is closely connected with their academic success in computer-based learning environments (Winters, Greene, & Costich, 2008). Research findings also show that online self-regulation is an essential factor guiding students' web-based information searching strategies (Tseng, Liang, & Tsai, 2014) and helps them organise and integrate information into viable mental models when learning online (Azevedo & Cromley, 2004). If students fail in online courses due to a lack of self-regulatory learning ability, they may exhibit insufficiency in goal commitment, locus of control, coping strategies, or resilience required to complete tasks (Artino, 2008;Cho & Shen, 2013).…”
Section: Self-regulation and Online Self-regulated Learningmentioning
confidence: 94%
“…Selfregulated strategies are beneficial in web-based learning (e.g., McLoughlin & Lee, 2010;Tseng, Liang, & Tsai, 2014). Learners who are more adapted to self-regulation develop better learning strategies and achieve better academic performances than those who lack self-regulation (Zimmerman & Kitsantas, 2014).…”
Section: Self-regulated Learning and Web-based Learningmentioning
confidence: 99%
“…In earlier hypotheses, job characteristics were deemed to be related to employees' web-based continuing learning, but may not directly impact it. Furthermore, several studies have suggested that self-regulated learning may be a mediator in the relationship between personal characteristics and online learning performance (e.g., Lin, 2011;Tseng et al, 2014). Hence, further research is needed to advance our understanding of how employees' job characteristics (i.e., work-related variables) and self-regulation (i.e., personal variables) affect their web-based continuing learning.…”
Section: Attitudes Towards Web-based Continuing Learningmentioning
confidence: 99%